Fall 2022 and Spring 2023 Summary of A2 (First-Year Composition) Courses with Embedded Multiliteracy Tutors (EMTs)
From July 2022 to December 2022 (fiscal semester), the University encountered enrollment drop: Fall 2022 recorded a total headcount of enrolled students at 5643, a drop of 12% from 6437 in Fall 2021. In addition, faculty and staff also identified student ennui--declining student engagement which inevitably impacted how students worked with embedded tutors and visited the WMC.